PENINGKATAN KAPASITAS ORANGTUA PADA SOTH (SEKOLAH ORANGTUA HEBAT) DALAM MENDIDIK ANAK TANGGUH MELALUI CHARACTER BUILDING - Grahani, Firsty Oktaria; Mardiyanti, Ressy; Lailiyah, Alfu Fitrotul; Rahardjo, Natasha Valentina (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Parenting is an important process in shaping and developing children's character, behavior, and social and emotional abilities. Parenting is a series of obligations that must be carried out by parents. If parenting cannot be fulfilled properly and correctly, it will lead to problems and conflicts, both within the child himself and between the child and his parents and the environment (Rakhmawati, 2015). The first environment a child encounters is a family consisting of father, mother and siblings. In their interactions, a child adapts what is seen and learned in the family. The problem that occurs is the lack of understanding of parents and families about appropriate parenting patterns for children, a limited understanding that affects the response or behavior of parents in parenting, especially when facing various problems in parenting so that sometimes it is not wise in acting, a limited understanding that also affects the attitude of parents who are less wise in behaving in parenting so that it often manifests inappropriate behavior from parents in parenting. This condition is the background for the focus of empowerment on increasing the capacity of parents in educating resilient children through character building. The solution and target outcomes to be achieved, namely providing psychoeducation through discussions to examine the accuracy of responses and attitudes possessed by parents in parenting so that parents can be wiser in responding, especially when experiencing obstacles in parenting; conducting role play and sharing sessions related to appropriate and effective parenting methods so that parents are more careful in their behavior when implementing parenting. The method used in increasing the capacity of parents is to use psychoeducation related to parenting, case studies, discussions and questions and answers, role play or simulation and sharing sessions and assistance in the form of counseling, especially if parents experience obstacles or problems in their implementation. The result is an increase in parents' understanding, especially in childcare, which can be observed through the results of the prepostest given; various psychoeducation methods provided through role play, sharing, and case studies make parents understand both through the material presented and sharing from fellow parents related to their experiences, so that they are able to improve inappropriate parenting patterns that have been applied at home.